Dispensasi Pernikahan Remaja dalam Hukum Islam dan Hukum Positif: (Satu Tinjauan Putusan Perkara No. 0505/Pdt.P/2020/PA.Pbg dan NO. 102/Pdt.P/2021/PA.PB) - Alfan Syafi'i; Fuji Astuti (El 'Ailaah, 2023)
Marriage dispensation is the granting of leeway to carry out marriage to prospective brides who have not reached the age requirements for marriage in accordance with the provisions of the Act. The judge in determining the decision of a case requesting a marriage dispensation is sometimes still difficult to understand the basis and considerations for the peoples. This study aims to determine the basis and considerations of the judge in the process of determining the application for a marriage dispensation, and to find out the comparison of the review of Islamic Law and Positive Law on the judge's decision in the case of the application for marriage dispensation at the Religious Court of Purbalingga Regency No. 0505/Pdt.P/2020/PA.Pbg and No. 102/Pdt.P/2021/PA.Pbg. The research method used by the author is qualitative research by combining two types of data, namely data obtained from field research in the form of observations, interviews and documentation at the Purbalingga Religious Court and added to library research in the form of judges' determination documents. About the dispensation of marriage. The data that the author obtained were then reduced, presented, and concluded using descriptive-comparative analysis techniques. Based on the research conducted, it is concluded that the basis of legal sources used by judges in the process of determining the application for marriage dispensation at the Religious Courts of Purbalingga Regency is Islamic law which is sourced from the Qur'an, Hadith, fiqh principles, and opinions of the fuqaha about the age limit for marriage. And Positive Law which is sourced from Law No. 50 of 2009, Law No. 16 of 2019, Perma No. 5 of 2019, Law no. 35 of 2014. The considerations used by the judge are based on the pillars and conditions of marriage, mental and physical readiness of the prospective bride and groom, the absence of obstacles / prohibitions on marriage, urgency, benefit for all parties, as well as the readiness of parents from both parties to guide the child. dispensation for marriage in the household. Based on the comparison, the determination of No. 0505/Pdt.P/2020/PA.Pbg is in accordance with applicable Islamic Law and Positive Law. While in the determination of case No. 102/Pdt.P/2021/PA.Pbg, the Positive Law used is appropriate, but if viewed from Islamic Law, the judge's decision on this case is still not appropriate because the two brides who will be married due to adultery have not received punishment (had) , and has not expressed repentance and regret for his actions.